Implementing Sales Force Tools Application OCTO Smart for Efficient Customer Bank Account Opening at CIMB Niaga Bank Surabaya: Implementasi Aplikasi Sales Force Tools OCTO Smart untuk Pembukaan Rekening Nasabah yang Efisien di Bank CIMB Niaga Surabaya - Dinda Nabila Leryzanti; Zumrotul Fitriyah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
CIMB Niaga Bank is one of the leading private banks in Indonesia. To meet its customer targets, CIMB Niaga innovates with digitalization to accommodate the interests of its customers, as well as facilitating its employees. CIMB Niaga created an application called OCTO Smart, which is designed as a tool for sales staff, so that they can work quickly and efficiently, such as for opening customer accounts. To see its real impact on CIMB Niaga employees and assess the performance of the application when used, a study was conducted to assess the quality of OCTO Smart. As a result, OCTO Smart succeeded in realizing its goal of helping its employees' work, but there were obstacles with the application, such as the camera feature and connectivity problems. The solution is that CIMB Niaga must continue to update its application so that it can work optimally. If this is implemented, CIMB Niaga employees will be able to continue using the application, the quality of their performance will increase, and customers will be satisfied.